ANALISIS MOTIVASI, KOMPENSASI, DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA PERAJIN TENUN TRADISIONAL ATBM DI KOTA PEKALONGAN - Alvis Muryo Dewanto (Jurnal Ekonomi Dan Bisnis, 2020)
This study is to determine and analyze the influence of motivation, compensation and job satisfaction on the job performance of weaving crafts. The hypotheses proposed in this study are: (1) motivation (X1), compensation (X2, and job satisfaction (X3) influence job performance (Y) of traditional weaver (ATBM). There were 50 respondents or weaving crafts. Hypothesis test was used with the F-test and t-test. The result of this research showed that motivation, compensation, and job satisfaction have a partial and simultaneous effect on job performance. Keywords: Motivation, Compensation, Job Satisfaction, Job Performance.